Research on Keyhole Diameter’s Vision Measurement Based on Parallel Technology - Zhang Chuan-chuan; Zeng Zhi-qiang; Wang Jun-yuan; Du Wen-hua (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
A keyhole diameter of the cartridge’s measurement based on machine vision is a part of the cartridge’s geometry measurement system, according to the system requirements, to complete the measurement within 5 seconds. A Image Collection System was constructed using computer, CCD camera, LED source, meanwhile a measurement system was compiled by C# on VS2010 platform based on machine vision. Use the Otsu algorithm to extracts the keyhole’s edge and near the pixels in order to reduce the computational Canny operator, and use parallel computing in the Canny operator to improve computing speed purposes. Use QueryPerformanceCounter timer for each module timing Canny operator, Canny operator improved computation time is reduced from the original 6s to nearly a hundred ms improved. Meet the time requirements of cartridge geometry measurement system, and other machine vision in which the project can be widely used.